2019
DOI: 10.2147/dddt.s203833
|View full text |Cite
|
Sign up to set email alerts
|

<p>Resveratrol reduces liver endoplasmic reticulum stress and improves insulin sensitivity in vivo and in vitro</p>

Abstract: Purpose : The aim of the study was to examine the effects of resveratrol upon hepatic endoplasmic reticulum stress (ERS) and insulin sensitivity in vivo and in vitro. Material and methods : C57BL/6J mice were fed a high-fat diet (HFD) for 8 weeks, and insulin resistance was evaluated by the intraperitoneal glucose tolerance test (IPGTT). Mice were then treated with resveratrol for 12 weeks and blood and liver samples collected. Blood biochemical indicators were determined by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 32 publications
2
28
0
Order By: Relevance
“…The accumulation of FFA and in particular overload with saturated fatty acids (SFA) trigger lipotoxicicty, lipoapoptosis, and finally IR development in the liver [ 11 , 12 ]. As a consequence, fatty degeneration in hepatocytes and increased levels of C-reactive protein (CRP) in circulating blood initiate the development of endoplasmic reticulum stress (ER stress) [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The accumulation of FFA and in particular overload with saturated fatty acids (SFA) trigger lipotoxicicty, lipoapoptosis, and finally IR development in the liver [ 11 , 12 ]. As a consequence, fatty degeneration in hepatocytes and increased levels of C-reactive protein (CRP) in circulating blood initiate the development of endoplasmic reticulum stress (ER stress) [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…When higher concentrations were used, only 10 µM DH-R and 25 µM R-4G induced significant effects. However, several authors have reported positive effects of resveratrol at higher concentrations (10–100 µM) in in vitro assays [ 46 , 47 ]. Indeed, Ji et al (2015) reported a reduction in triglyceride levels in AML12 cells from 25 to 100 μM of resveratrol.…”
Section: Discussionmentioning
confidence: 99%
“…Resveratrol could boost glucose uptake in the absence of insulin (Zhao et al, 2019). It also exerts an anti-diabetic property via enhancing mitochondrial function and an anti-aging property via promoting energy expenditure (Ren et al, 2017;Zou et al, 2017).…”
Section: Resveratrolmentioning
confidence: 99%